The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1128/jb.112.1.649-652.1972
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Irradiated Medium for Repair-Deficient Strains of Escherichia coli

Abstract: Nutrient agar medium is made highly toxic to certain repair-deficient strains of Escherichia coli by exposure of the uninoculated plates to radiation from cool-white fluorescent lamps or black-light fluorescent lamps. This sensitivity is associated with the genetic deficiencies, fil, phr, and recA. Repair-sufficient and uvr strains are only slightly affected by the irradiated media. The poor growth and reduced plating efficiency frequently associated with BPhr and recA strains are very likely caused by inadver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Our results parallel those of Webb and J,orenz (4) who report that preirradiation of nutrient medium produces a toxicity associated with the genetic deficiencies fil, phr, and recA in E. coli. They also noted that uvr and other repair-sufficient strains of E. coli are not sensitive to preirradiated medium, that recA and fil strains are more sensitive to medium preirradiated with black light than visible light, although the phr mutant is very sensitive to medium preirradiated with visible light (4).…”
supporting
confidence: 91%
“…Our results parallel those of Webb and J,orenz (4) who report that preirradiation of nutrient medium produces a toxicity associated with the genetic deficiencies fil, phr, and recA in E. coli. They also noted that uvr and other repair-sufficient strains of E. coli are not sensitive to preirradiated medium, that recA and fil strains are more sensitive to medium preirradiated with black light than visible light, although the phr mutant is very sensitive to medium preirradiated with visible light (4).…”
supporting
confidence: 91%
“…The existence of a class of nonviable but residually dividing cells resolves the apparent discrepancy between the effects of rec mutations on growth rates versus viabilities: the intermediate class of cells contributes to the mass increase of the culture, but not to the viability. Furthermore, our results indicate that the inviability of Recstrains does not result from an increased sensitivity of these strains either to the manipulations associated with plating cells on solid medium or to possible chemical changes that may occur when agar medium is exposed to fluorescent room lighting (20).…”
Section: Discussionmentioning
confidence: 79%
“…Changes in ionic strength, temperature, and richness of medium do not affect viability, nor does the irradiation given off by fluorescent room lights during the growth of the cultures (4). It has been suggested that pre-irradiation of' the agar medium by fluorescent room lights may lower recAviability (20).…”
mentioning
confidence: 99%
“…If BL damage is mediated by an endogenous photosensitizer (1), the chromophore involved must be highly specific for near-UV radiation since little inactivation by CW was observed. Several candidates for a near-UV chromophore have been proposed (13,25). That the BLinduced lethal lesions are not cyclobutyl pyrimidine dimers is suggested by the observation that PR does not enhance survival of N. crassa after BL irradiation (data not presented).…”
Section: Resultsmentioning
confidence: 99%